Putting "Perspectives" in Perspective: Literary Fiction, Empathy & Diversity In the Public Affairs Classroom. (4th May 2021) - Brainard, Lori A.
Abstract : In the context of increasing diversity, polarized politics, and degraded public discourse, public servants are more central than ever to democracy. What new skills might they need? How might we address them in our curricula? This article analyzes one attempt: "Perspectives on Public Values, " a course that fosters empathy in difficult conversations about diversity, equity, and inclusion (DEI) while relying on literary fiction as its material. To draw lessons for programs offering similar courses, it assesses the student experience, focusing on: concerns students had before the course; whether those concerns manifested in the course; what most surprised students; what the instructor should do differently/the same in the future; and the students' main lessons. Data come from students' written reflections and the instructor's reflection. This study finds: more students voiced concerns about the DEI aspect of the course than about its basis in literary fiction; in the future the instructor should make stronger connections to public administration; and students' reported increased self-awareness, and derived lessons about the importance of multiple perspectives and lived experiences, and implications for public service practice. It concludes with recommendations for pedagogy, workplace training, and how public administrators might view DEI issues.